2014
DOI: 10.1016/j.clim.2013.12.002
|View full text |Cite
|
Sign up to set email alerts
|

A T cell gene expression panel for the diagnosis and monitoring of disease activity in patients with systemic lupus erythematosus

Abstract: Systemic Lupus Erythematosus (SLE) remains a challenging disease to diagnose and follow, as no reliable biomarkers are known to date. We designed a gene expression panel with 40 genes known to play a role in SLE pathogenesis. We found that the combined expression of these genes in SLE T cells can accurately differentiate SLE from healthy individuals and patients with other autoimmune diseases. The accuracy of the test increased further (83%) when only three out of the initial genes (OAS2, CD70 and IL10) were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…However, apart from the anti-virus function, OAS family proteins may be also related to SLE pathogenesis. Grammatikos et al suggested that combining the expression levels of OAS2, CD70, and IL10 in T cells can be used for diagnosis and monitoring of disease activity in SLE patients (14)(15)(16). A ''T-cell score'', which was created with the three gene panel, was significantly higher in SLE patients than in the healthy control group and correlated significantly with dsDNA, PGA, SLEDAI, and ESR levels (14).…”
Section: Discussionmentioning
confidence: 99%
“…However, apart from the anti-virus function, OAS family proteins may be also related to SLE pathogenesis. Grammatikos et al suggested that combining the expression levels of OAS2, CD70, and IL10 in T cells can be used for diagnosis and monitoring of disease activity in SLE patients (14)(15)(16). A ''T-cell score'', which was created with the three gene panel, was significantly higher in SLE patients than in the healthy control group and correlated significantly with dsDNA, PGA, SLEDAI, and ESR levels (14).…”
Section: Discussionmentioning
confidence: 99%
“…Necrotic cell death is overall increased in SLE patients due to oxidative stress-induced mTOR-dependent expansion of CD3 + CD4 − CD8 − double-negative (DN) T cells [29,30]. These T cells also play critical roles in pathogenesis of SLE patients [31]. Importantly, DN T cells are expanded in the liver of lupus-prone mice [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Healthy sex-and age-matched control cells were also used for experiments herein. Briefly, peripheral venous blood was collected in heparin-lithium tubes and PBMCs were prepared with Ficoll-Paque centrifugation, as previously described (84).…”
Section: Methodsmentioning
confidence: 99%